Comparative study of teachers' and students' attitude to the introduction of sex education into secondary schools in Ibadan (2014)
This study examined the attitude of teachers and students to the introduction of sexuality education in secondary schools in Ibadan metropolis. The sample was made up of 40 teachers and 160 students randomly selected from 4 (2 private and 2 government owned) secondary schools m Ibadan. An 8-itemed self-designed questionnaire ‘Teachers and Students Attitude to Sexuality Education Questionnaire’ (TSASEQ) with 0.71 reliability was used in collecting data for the study. Data collected were analyzed using simple percentages and frequency counts. Results showed that the attitude of majority of teachers and students towards introduction of sexuality education in secondary schools is negative. Responses to typical items on the questionnaire showed that 65% of teachers and 68.75% of students believe that sexuality education can lead to increased immorality among children as 67.5% of teachers and 70% of students feel sexuality education will prematurely expose students to information about sex. Also, 55% of teachers and 64.37% of students indicated that they will feel embarrassed to teach or learn about sexuality in class. It was recommended that in-service training be provided for the teachers to develop adequate skills needed to teach sex and relationship education in a family life oriented manner. Also, awareness programmes should be organized in schools for teachers and students on the importance of sexuality education in curbing irresponsible sexual behavior which is capable of truncating immediate and future academic or career plans of the students.